Exploring Halal Tourism as Indonesia’s Super-Priority Destination: Muslim Travelers’ Needs in Labuan Bajo - Nurkarim, Muhammad Azmi; Nursyabani, Cahyania; Fatwa, Nur; Rini, Nova; Ramy Azhar, Muhammad (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2025)
Introduction: This research aims to explore the needs of Muslim travelers who visit the Super-Priority Destination of Labuan Bajo. Labuan Bajo is considered one of the potential destinations for developing halal tourism in Indonesia. However, the predominance of a non-Muslim population in the region presents a distinctive challenge in the implementation and promotion of halal tourism practices. Methods: The approach used is qualitative, with data collected through in-depth interviews with Muslim Traveler informants who had visited Labuan Bajo. The in-depth interview questions are based on the extension of the theory of travel. Results: The research results show that the main motivations for Muslim travelers visiting this place are recreation and work, where natural beauty and ease of access are the main factors attracting Muslim tourists to visit this place. However, there are still many challenges that need to be addressed, such as the limited availability of prayer facilities in some island destinations, the lack of halal-certified food options, and the insufficient communication between tour providers and tourists. Conclusion and suggestion: This study concludes that Labuan Bajo is a Muslim-friendly destination, but the improvement of worship facilities and halal food must be optimized. This research is expected to serve as a foundation for the development of halal tourism in predominantly non-Muslim destinations that are inclusive and sustainable.